SOCIAL MOBILITY AND PERSONAL IDENTITY IN GREAT EXPECTATIONS - Razzaqova Madinaxon Iqboljon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article analyzes the theme of social mobility and its influence on personal identity in Great Expectations by Charles Dickens. The novel presents the psychological transformation of Pip, whose desire for higher social status reshapes his moral values and relationships. Through qualitative literary analysis, this study examines how Dickens critiques Victorian class structure and demonstrates that true maturity is achieved through ethical awareness rather than material success. The findings show that social ambition leads to internal conflict, but moral self-realization ultimately defines authentic growth.